Healthy cravings? Impact of imagined healthy food consumption on craving for healthy foods and motivation to eat healthily - Results of an initial experimental study. (1st April 2023) - Werthmann, Jessica; Tuschen-Caffier, Brunna; Ströbele, Leonie; Kübel, Sebastian L.; Renner, Fritz
Abstract: Craving for high-calorie foods predicts consumption of high-calorie foods thereby contributing to unhealthy eating habits and, potentially in the long term, to the development of overweight, obesity, and eating disorder pathology. Thus, effective interventions tackling craving for unhealthy foods and motivating healthy eating behavior are needed. This initial study tested if an experimental mental imagery procedure could induce craving for healthy foods and increase the motivation to eat healthily. Participants (N = 82) were randomized to either a healthy craving mental imagery condition or to a neutral mental imagery control condition. Craving for healthy foods and motivation to eat healthily was assessed before and after the experimental manipulation via self-report. A (disguised) food choice for healthy versus unhealthy food was added as a behavioural measure at the end of the experiment. Repeated measures of variance analyses with time (pre vs. post experimental manipulation) and condition (healthy craving mental imagery versus neutral mental imagery) yielded significant interactions for healthy craving and motivation to eat healthily: Post-hoc tests showed that craving for healthy foods and motivation to eat healthily increased significantly after the experimental manipulation in the healthy craving mental imagery condition, but not in the neutral mental imagery condition. Results of this initial study suggest that an experimental mental imagery induction of craving for healthy food leads to an increase in healthy craving and motivation to eat healthily. Further experimental research is needed to rule out priming effects, to test the underlying mechanisms of this effect, and evaluate the potential of this mental imagery procedure in a clinical context.